Retrieval Performance for USIM’s Quranic Search Engine - Basir, Nurlida; F. Nabila, N.; Juana Mohd Zaizi, Nurzi; Mohd Saudi, Madihah; Ridzuan, Farida; Ali Pitchay, Sakinah (International Journal of Engineering and Technology, 2018)
The Quran covers every field of life namely medical, political, social, economic, and others. The extraction of quranic knowledge is a challenging task, as the Quran is rich in its linguistic and multi-layered meanings, difficult if done without the use of other resources such as the Hadith and Tafsir by Muslim Scholars. Several Quranic ontologies have been developed, however, most of these only focus on certain domains and language, rather than the content of the Quran. In many cases, the searching cannot retrieve the relevant fields. Discovering the fields of a keyword searched in the Quran can become a guidance to enhance knowledge in a particular domain. In this paper, we propose that the keyword searched in the Quranic ontology can be applied for extracting the relevant fields. For this purpose, exploratory search has been done. The sample domain ontology based on the medical and economic fields mentioned in the Quran has been developed in TopBraid Composer. Queries have been run to depict the proper role of ontology.Â Then, certain recommendation for the proposed Quranic ontology attaining semantic search from all domains and the result by searching from verse to domain, or domain to verse, has been proposed.Â Â